Peranan Duta Besar Keliling Berdasarkan Konvensi New York 1969 Tentang Misi Khusus - Muhammad Yogi Nofran; M. Azzah Rozanda (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Contemporary diplomacy faces complex challenges that demand flexibility in the implementation of international relations. As part of a special mission, a traveling ambassador plays a strategic role in bridging the interests of the sending state and the receiving state for specific and temporal purposes. The 1969 New York Convention on Special Missions provides a comprehensive legal framework governing the position, functions, rights, obligations, and immunities and privileges of a traveling ambassador. This study analyzes the role of a traveling ambassador, focusing on the provisions of the 1969 New York Convention and its implementation in the diplomatic practices of countries. Using normative legal research methods with a legislative and conceptual approach, this study finds that the 1969 New York Convention provides a clear yet flexible legal basis for the operationalization of a traveling ambassador. The legal status of a traveling ambassador is systematically regulated from appointment and accreditation to the end of the mission. The main functions include representation, negotiation, information gathering, and reporting with specific territorial and time limits. The rights and obligations of a traveling ambassador are formulated in a balanced manner, providing operational facilities while requiring respect for the laws of the receiving state. The immunities and privileges granted are equivalent to those of permanent diplomats, but with a limited duration, consistent with the term of the special mission. The implementation of the convention's provisions has demonstrated its effectiveness in supporting bilateral and multilateral diplomacy, despite challenges related to coordination with permanent diplomatic missions and the limited availability of global ratification.